Analysis of the efficacy of holmium laser and pneumatic ballistic in the treatment of impacted ureteral calculi. Issue 36 (4th September 2020) - Chunlin, Yang; Wanlin, Du; Jinhua, Du
Abstract : Abstract: To explore the safety and effectiveness of ureteroscopic holmium laser lithotripsy (UHLL) and ureteroscopic pneumatic lithotripsy (UPL) in the treatment of impacted ureteral calculi (IUC). Clinical data of 280 patients in our hospital from April 2016 to May 2019 were retrospectively collected and analyzed, including 136 cases of UHLL group and 144 cases of UPL group. The general clinical data, operation time, intraoperative bleeding volume, hospital stay, stone-free rate (SFR), and surgical complications were collected and analyzed in 2 group. Compared with UPL group, the operation time of UHLL group was significantly reduced (27.25 ± 8.39 vs 34.32 ± 10.57, P  < .05), but the hospitalization cost was significantly increased (9.25 ± 0.75 vs 8.24 ± 0.51, P  < .05). In terms of total SFR, the UHLL group was significantly higher than the UPL group (93.38% vs 83.33%, P  = .011). For proximal IUC, compared with the UPL group, the SFR of the UHLL group was significantly increased (88.33% vs 70.31%, P  = 0.005). For distal IUC, there was no significant difference in SFR (97.37% vs 93.75%, P  = .638) between the UHLL group and UPL group. There were no significant differences in the complications of local mucosal injury, hematuria, febrile urinary tract infection, ureteral perforation, and urinary sepsis in the 2 groups ( P  > .05). However, the UHLL group was significantly lower in stone residual rate than the UPL group (6.61% vs 16.67%, P  = .001). This study found that UHLL and UPL are safe and effective in the treatment of IUC, but UHLL has the advantages of shorter operation time and high SFR in the treatment of IUC.